2021
DOI: 10.1089/brain.2020.0899
|View full text |Cite
|
Sign up to set email alerts
|

Regional Strength of Large-Scale Functional Brain Networks is Associated with Regional Volumes in Older Adults and in Alzheimer's Disease

Abstract: Background: The association between regional volumes and resting-state functional networks was tested within the default-mode network (DMN), influenced by Alzheimer pathology, salience network (SalN), not under similar pathological influence, and sensorimotor network (SMN), usually spared by pathology. Methods: A total of 148 participants, with Alzheimer's disease (AD) dementia, mild cognitive impairment (MCI), and healthy controls underwent multimodal brain magnetic resonance imaging (MRI). Functional network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…This pattern of alteration among these networks' dynamic interactions was observed in association with all aspects of anosognosia in this study. Changes in inter-network activity expressed as increased connectivity between the DMN and the salience network, also found in this study in association with anosognosia, have been previously reported in mild probable AD dementia (Sarli et al, 2021). It might be suggested, therefore, that changes in activity in anticorrelated networks would alter the level of mutual inhibition exerted among their regions leading to a progressive loss of network integration and, in turn, to detectable cognitive and functional impairments, including alterations of awareness.…”
Section: Subcortical Contributions To Anosognosiasupporting
confidence: 86%
“…This pattern of alteration among these networks' dynamic interactions was observed in association with all aspects of anosognosia in this study. Changes in inter-network activity expressed as increased connectivity between the DMN and the salience network, also found in this study in association with anosognosia, have been previously reported in mild probable AD dementia (Sarli et al, 2021). It might be suggested, therefore, that changes in activity in anticorrelated networks would alter the level of mutual inhibition exerted among their regions leading to a progressive loss of network integration and, in turn, to detectable cognitive and functional impairments, including alterations of awareness.…”
Section: Subcortical Contributions To Anosognosiasupporting
confidence: 86%
“…The brain areas of the SN were summarized as follows: (1) Use ICA: bilateral anterior insula (Yi et al, 2015 ), bilateral frontoinsular cortex, bilateral anterior cingulate cortex (ACC) (Han et al, 2011 ), bilateral dorsal ACC (dACC), bilateral insula lobule (Chand et al, 2017 ), right supplementary motor area (SMA), left superior temporal gyrus (STG), bilateral supramarginal gyrus (SG), left precuneus (Conwell et al, 2018 ; Cai et al, 2020b ), preSMA (Yi et al, 2015 ), dorsal anterior cingulate cortex/medial prefrontal cortex (dACC/MPFC), dorsolateral prefrontal cortex (DLPFC) (He et al, 2014 ), bilateral caudate (Agosta et al, 2012 ), the thalamus (Wang et al, 2020 ), bilateral ventrolateral prefrontal cortex, bilateral STG/insula, midcingulate cortex/preSMA, medial orbitofrontal cortex, and bilateral orbital/frontoinsular (Agosta et al, 2012 ) and (2) Use seed ROI: bilateral frontoinsular cortex (Joo et al, 2017 ), bilateral anterior insula, bilateral dACC, dACC/MPFC, bilateral anterior insula (Zhu et al, 2016 ), bilateral insula (Sarli et al, 2021 ), and bilateral SG (Liang et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been proposed that the pattern of regional atrophy typically seen in ageing may act as a promoter of functional plasticity, because task activation in older adults tends to increase in areas that are subjected to age-associated volumetric decrease (Greenwood, 2007). A recent study confirmed this negative association between regional structure and network expression in healthy adults, and also found inverse (positive) associations in patients with AD, indicating that those with reduced atrophy were also those with a stronger network expression (Sarli et al, 2021). Within this context, WMHs are a further contributor to the reorganisation of the neurofunctional architecture, as reported by a number of investigations (Reijmer et al, 2015;Zhou et al, 2015;Cheng et al, 2017;De Marco et al, 2017b;Liu et al, 2019).…”
Section: Discussionmentioning
confidence: 90%